Rizzoli & Isles Season 6 Disc 4 - Harmon, Angie, 1972-; Alexander, Sasha, 1973-; Bridges, Jordan, 1973-; Victor, Idara; McGill, Bruce, 1950-; Hanes, Ken; Strand, Mark; Nash, Jan; Wech, Katie; Sardo, Michael; Prange, Greg; Warner Bros. Entertainment; et al. (Burbank, CA Warner Bros. Entertainment, 2016)
Hundreds of threatening emails. Credit accounts hacked. Her apartment burned. A death message found inside a murder victim. Someone has it out for Detective Jane Rizzoli in Season Six, and she's consumed with finding out who. As clues keep coming and Jane is assigned a bodyguard, Boston's finest are put on the case in a race against time, until medical examiner Dr. Maura Isles disappears, victim of a possible kidnapping.
Episode 16. East neets West (3/1/16) / written by Ken Hanes ; directed by Mark Strand -- episode 17. Bomb boyage (3/8/16) / written by Jan Nash & Katie Wech ; directed by Jan Nash -- episode 18. A shot In The dark (3/15/16) / written by Michael Sardo ; directed by Greg Prange.
Title from container.
Widescreen (1.78:1).
Special features: From the shadows: a criminal revealed.
Angie Harmon, Sasha Alexander, Jordan Bridges, Idara Victor, Bruce McGill.
Rating: Not rated.
DVD.
Keywords: Isles, Maura -- (Fictitious character); Rizzoli, Jane, -- Detective (Fictitious character); Medical examiners (Law) -- Massachusetts -- Boston -- Drama; Women detectives -- Massachusetts -- Boston -- Drama; Forensic pathologists -- Massachusetts -- Boston -- Drama; Criminal investigation -- Massachusetts -- Boston -- Drama; Massachusetts -- Boston; Drama; Television cop shows; Television crime shows; Video recordings for the hearing impaired